An experimental investigation into scope rigidity in written Mandarin - Wu, Hongchen (Frontiers in Psychology, 2023)
Mandarin Chinese is claimed to be a scope-rigid language, as its doubly-quantified simple transitive sentences are unambiguous with surface scope only and no inverse scope available. However, it has been debated whether Mandarin Chinese allows inverse scope in some syntactic environments other than simple transitives. This paper investigates whether scope rigidity as a property of the grammar of Mandarin prevents scope ambiguity in different syntactic environments and what factors influence scope interpretations. Using a Truth-Value Judgment task, we tested the judgments of 98 Mandarin Chinese native speakers on transitive sentences containing both a subject and object quantifier under adverbial clauses. The results show that inverse scope reading is considered available for doubly-quantified transitives under adverbial clauses, although there are intra-participant variances. The results challenge the well-established approaches to quantifier scope in Mandarin and call for rethinking the long-standing dichotomy view of quantifier scope in languages. We also found bimodal distribution on the acceptance of inverse scope readings, suggesting that there may be two different populations of native speakers with two different grammars. In addition, we also observed other factors that may affect scope behaviors, including clause type, presence of aspect marker, verb type, and numbers.